2022
DOI: 10.1108/medar-07-2020-0946
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate governance on integrated reporting (IR) quality and sustainability performance: evidence from listed companies in South Africa

Abstract: Purpose This study aims to examine the relationship and effect of integrated reporting (IR) quality on sustainability performance and explore the relationships and effects of corporate governance mechanisms on IR quality and sustainability performance. Design/methodology/approach Partial least squares structural equation modelling (PLS-SEM) was used in a longitudinal study by following the steps in Roemer’s Evolutionary Model on a sample of listed companies on the Johannesburg Stock Exchange (JSE) in South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 103 publications
4
22
0
Order By: Relevance
“…Flower, 2015;Thomson, 2015). However, emerging empirical evidence suggests that there is value in IR in terms of promoting the sustainability behaviour of firms (see Appiagyei et al, 2022;Le Roux and Pretorius, 2019;Omran et al, 2021). These empirical findings affirm the assertions of the IIRC that IR promotes both financial and sustainability performance.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Flower, 2015;Thomson, 2015). However, emerging empirical evidence suggests that there is value in IR in terms of promoting the sustainability behaviour of firms (see Appiagyei et al, 2022;Le Roux and Pretorius, 2019;Omran et al, 2021). These empirical findings affirm the assertions of the IIRC that IR promotes both financial and sustainability performance.…”
Section: Introductionmentioning
confidence: 57%
“…In relating IR to sustainability, prior research on the effect of IR on sustainability performance provides evidence of a positive association between IR and sustainability performance (see Appiagyei et al, 2022;Le Roux and Pretorius, 2019;Omran et al, 2021). Le Roux and Pretorius (2019) use a single case study of a JSE-listed firm to investigate the link between IR and sustainability embeddedness.…”
Section: Ir and Sustainability Performancementioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have examined the relationship between the characteristics of the board of directors, audit committee characteristics, firm characteristics and IR practices. For MEDAR 31,6 example, Appiagyei et al (2022) aimed to explore the relationships and effects of corporate governance mechanisms on IR quality and sustainability performance. The study reported that the board effectiveness and external audit quality have significant effects on IR quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stakeholder theory contends that a firm must care for and should be accountable to a wider set of stakeholders, not merely shareholders (Freeman, 1984;Appiagyei et al, 2016). Instead of focusing exclusively on maximising shareholders' wealth, a firm must strive to satisfy all the stakeholders who are critical for a firm's success.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%